Surficial Failure of Expansive Soil Cutting Slope and Its Flexible Support Treatment Technology - Jie Xiao; He-ping Yang; Jun-hui Zhang; Xian-yuan Tang (Advances in Civil Engineering)
The surficial failure of most expansive soil cutting slopes, subjected to the repeated wet-dry cycles, often occurs during or after rainfall following a long drought. The reason for this, however, is still unclear. Therefore, the laboratory tests were conducted to gain the saturated drained shear strength of the natural Nanning expansive soil considering the combined effects of swelling with loading and wet-dry cycles. The findings indicate that the envelope of shear strength, which significantly drops close or equal to zero, can be well fitted by the generalized power function. At the same time, the effect of shear strength parameters on the stability of the expansive soil cutting slope was investigated. The reasons for the shear strength attenuation of the natural expansive soil and the surficial failure of the expansive soil cutting slopes were analyzed. It is evident that the effective cohesion being small is a vital factor influencing the occurrence of surficial failure of an expansion soil slope. Moreover, an effective flexible support treatment measure was provided.